Hydrothermal Treatment of Palm Oil Mill Effluent (POME) under Oxidative and Non-oxidative Conditions - Zhan, Sheng Lee; Chin, Kui Cheng; Chin, Sim Yee (IOP Publishing, 2020)
The performances of oxidative (OHT) and non-oxidative (NOHT) subcritical hydrothermal treatments of palm oil mill effluent (POME) were investigated. The experiments were performed in a pressurised 500 mL-autoclave at different temperature (493 K – 533 K) and reaction time (2 h – 8 h). At 533 K and 8 h, the OHT reaction showed the highest removals of 5-day biochemical oxygen demand (BOD5) and chemical oxygen demand (COD), recording 87.30% and 71.23% respectively, with the pH of liquid product attained 6.5 from an initial value of 3.5. The reduction of COD and BOD5 in NOHT was lower than that in OHT, which were 61.43% and 68.02%, respectively. The mechanism of OHT reaction was via the free radical's pathway. In contrast, the organic compounds originally present in POME degraded into water-soluble products, accompanied by deoxygenation that consisted of decarboxylation and dehydration during the NOHT.